Sport and leisure public policy in nova lima: from agenda setting to implementation (Research, Society and Development, 2022)
Studies on the topic of public policies have grown in the academic environment. Understanding the policies developed in our reality is an important step in this direction. This text aims to analyze the implementation process of the public policy of sports and leisure in the city of Nova Lima. It ranges from the identification of the problem and the establishment of the political agenda for the issue. The used methodology was the analysis of documents and semi-structured interviews with the managers of the Municipal Secretariat of Sports and Leisure - SEMEL, of the city of Nova Lima in the past two administrations. As results we can consider that the agenda is formed from the demand arising from different spaces and subjects, characterizing visible players influencing decision making as to which problems or issues will comprise the political agenda. It is feasible to consider that sports and leisure policies in the city of Nova Lima are close to the top down model.